Bridging Research and Digital Strategy: A Narrative Review of R&D–IT Integration - Pebriana, Yosi; Lovez, Gevin Rivauldy; Nurshandy, Aries; Nashrullah, Fahmi Rizqi; Azi, Rizal Ibrahim (Indonesian Scientific Publication, 2025)
The integration of research and development (R&D) with information technology (IT) strategies has become increasingly vital for high-tech firms in navigating global competition and rapid digitalization. This narrative review aims to evaluate how R&D–IT alignment influences innovation performance, organizational efficiency, and long-term competitiveness. A systematic narrative review approach was employed by analyzing peer-reviewed studies published in the last fifteen years that addressed R&D–IT interactions across various industries. The analysis focused on identifying key drivers, barriers, and systemic conditions shaping integration outcomes. Findings indicate that IT strategies consistently enhance R&D performance, demonstrated by increases in patent generation, shorter product development cycles, and improved customer satisfaction. Internal factors such as digital capabilities, transformational leadership, and innovation-oriented organizational culture further strengthen integration effectiveness. At the systemic level, supportive government policies, intellectual property protection, and stable regulatory frameworks provide enabling conditions for sustainable collaboration. Nevertheless, challenges including technological misalignment, cultural resistance, and limited infrastructure in developing economies remain significant obstacles. The implications of this review highlight the importance of policy incentives, workforce digital skill development, and stronger public–private collaborations to overcome systemic and organizational barriers. Future research should explore cultural and contextual dynamics in greater depth, particularly within emerging economies, to provide a more comprehensive understanding of how R&D–IT integration fosters sustainable innovation and competitiveness.